Fatores associados à experiência e dor durante o trabalho de parto e parto vaginal de mulheres brasileiras: estudo transversal - Figueiredo, Alice Moralez de (Universidade Federal de São Carlos, 2023)
Introduction: Vaginal birth pain can be an important factor that contributes to the reduction of vaginal birth rates in the world. Objective: To analyze the factors associated with the painful sensation and the experience of pain in Brazilian women during the labor and vaginal delivery. Methods: Cross-sectional study, which included women up to three months postpartum. Data collection was carried out online using "Google Forms", through two semi-structured questionnaires that included questions about sociodemographic characteristics, presence of comorbidities and obstetric history of the participants, in addition to assessing conditions related to the last labor and delivery. The women completed the Numerical Pain Scale (END) to assess the intensity of pain during labor and delivery. Furthermore, the Childbirth Experience Questionnaire (CEQ-Br) was used to assess conditions related to happiness, a sense of security and control of the woman's situation, trust in the team and the presence of positive or negative memories of childbirth. The modified Delphi method was used in the formulation of semi-structured questionnaires with questions based on knowledge previously described in the literature about factors associated with pain during labor and vaginal delivery. Data analysis: Data were analyzed using the SPSS software using multiple linear regression analysis (enter method), with a 95% confidence interval, and Pearson's chi-square test to verify the outcomes of childbirth experience and pain. Results: Follow-up physical therapy during the gestational period, using a vaginal dilator (Epi-no), the woman being in a public hospital/maternity, receiving a relaxing massage and having the assistance of a doula are positive predictors of the women's childbirth experience,while the presence of complications, the use of oxytocin and the lack of assistance during labor and delivery are negative predictors of the women's childbirth experience. There is a relationship between mild pain during labor, and mild and severe pain, and the woman being in a public hospital/maternity. Conclusion: There are positive and negative predictive factors for vaginal delivery in Brazilian women.
Factors associated with experience and pain during labor and vaginal delivery of brazilian women: cross-sectional study
Keywords: Trabalho de parto; Parto vaginal; Dor; Saúde da mulher; Vaginal delivery; Pain; Women´s health; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL